Resistência de união de sistemas adesivos ao esmalte adjacente a cavidades submetidas à remoção seletiva de tecido cariado - Pires, Carine Weber (2018)
This work is composed by three studies, whose main themes are adhesion and minimally invasive Dentistry. Manuscript 1: Can area delimitation and tube type impact microshear bond strength of adhesives to dental substrates? This work evaluated the need of delimitation of the adhesive area and of tube type used in the creation of the composite resin specimens for microshear bond strength test (μSBS). 120 bovine incisors were prepared and randomized in groups according to a) substrate: enamel (n=60) and dentin (n=60); b) adhesive systems: Clearfil SE Bond-CSE, Single Bond Universal-SBU- etch-and-rinse and self-etching; c) adhesive area: with delimitation and without delimitation; d) tube type: starch and polyethylene. After the μSBS assay, data were submitted to three-way ANOVA and Tukey’s test (α=0.05). The area delimitation did not influence the bond strength values, regardless of the substrate. The tube type influences the bond strength of material and substrate-dependent mode. Thus, as a simplified methodology of μSBS, it is possible to use starch tube without delimiting the adhesive area. Manuscript 2: Is adhesive bond strength similar to primary and permanent teeth? A systematic review and meta-analysis. This work elucidated the need for inclusion of primary and permanent teeth in studies of bond strength, due to the microstructural differences between both. The aim of this paper was to systematically review the literature for laboratory studies to determine whether the bond strength values obtained to primary teeth are similar to permanent ones. The meta-analysis included 37 studies and the results showed that permanent teeth presenting higher bond strength values than primary teeth. Considering each substrate individually, the difference was significant only for dentin. Therefore, the bond strength values obtained in permanent tooth enamel can be considered in extrapolation for primary teeth. Manuscript 3: Bonding of three adhesive systems to enamel surrounding real-life cavities after selective removal of carious tissue. This study evaluated the influence of enamel condition – sound or supposedly demineralized (adjacent to cavitated caries lesions submitted to selective removal of carious tissue) – in the bond strength of adhesive systems. 28 permanent molars (n=7) with dentin caries lesions were prepared and three adhesives – SBU (etch-and-rinse and self-etching strategies), Adper Single Bond Plus and CSE - were applied to the enamel around the margin of cavity and in the sound enamel, distant to caries lesion. The μSBS assay was performed and the data were submitted to two-way ANOVA and Tukey’s test (α=0.05). The values of μSBS to the enamel surrounding cavities were smaller than to the enamel far from the margins, regardless of the adhesive system used. Thus, enamel with suspected of mineral loss may jeopardize the adhesion and it is indicated to remove this enamel with rotating instruments in high rotation before adhesive procedures.